Implementasi Total Quality Management Dalam Meningkatkan Mutu Pendidikan di MTs Negeri 1 Palembang - Hendri Purnama Sari; Ida Fitri; Asri Karolina; Saipul Annur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving the quality of education at MTs Negeri 1 Palembang. The background of this research is based on the importance of improving educational quality in the era of globalization, which requires educational institutions to be competitive and produce high-quality graduates. TQM is considered an effective management approach to continuously improve quality through the involvement of all organizational members, customer focus, and continuous improvement. This study employs a qualitative approach with a descriptive research design. The research was conducted at MTs Negeri 1 Palembang, involving the head of the madrasa, teachers, educational staff, and students as research subjects. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of TQM at MTs Negeri 1 Palembang has been carried out effectively through the application of key principles, including customer focus (students and parents), effective leadership, involvement of all school members, and continuous improvement.